Dendrites‐Free Lithium Metal Anode Enabled by Synergistic Surface Structural Engineering. (3rd March 2022) - Di, Jie; Yang, Jin‐Lin; Tian, Han; Ren, Pengfei; Deng, Yirui; Tang, Wenhao; Yan, Wenqi; Liu, Ruiping; Ma, Jianmin
Abstract: Lithium (Li) metal with high specific capacity and low redox potential is widely considered as a potential anode for lithium‐ion batteries (LIBs) with high energy density. However, the catastrophic dendrites growth, "dead Li" formation, and surface passivation hinder its practical application. Herein, a selective artificial solid electrolyte interphase (SEI) layer (Li2 S x, x = 1, 2) protection strategy is adopted, where the tip sites passivation and the uniform Li nucleation in grooves are well combined, which enables reversible Li stripping/plating with high storage capacity and robust electrode framework. The grooves derived patterned array Li with selective Li2 S x artificial SEI (LS@A‐Li) exhibit over 1800 h cycling life at 1.0 mA cm –2 /1.0 mAh cm –2 and over 600 h even under 5.0 mA cm –2 /10.0 mAh cm –2 . The application feasibility of such LS@A‐Li is also confirmed by coupling with commercial LiFePO4 and LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) in the full batteries. This work paves way for the large‐scale application of Li metal anode in lithium‐metal batteries with a facile and efficient fabrication process. Abstract : The array lithium anode with selective coverage of artificial SEI (LS) is fabricated by cleverly compounding physical calendaring and low‐temperature gas‐solid reaction on the lithium foil. The two modifications complement each other in this strategy to induce uniform lithium deposition at both low and high current densities, and the LS@A‐Li anode is able to work stably for a long time.